A comparative study of dexmedetomidine and fentanyl as adjuvants to ropivacaine on analgesic efficacy in supraclavicular brachial plexus block - Debnath, Malin; Singh, Takhelmayum Hemjit; Singh Thokchom, Rupendra; Kirha, Nongosal; Das, Mahasweta; Pious, Pabin (International Journal of Research in Medical Sciences, 2023)
Background: Various adjuvants have been added to improve the quality of the supraclavicular brachail plexus block and prolong postoperative analgesia. The aim of the present study was to compare the onset and duration of sensory and motor blockade provided by dexmedetomidine and fentanyl as adjuvants to ropivacaine in such block. Methods: In this study 60 patients with American Society of Anesthesiologists grade I/II scheduled for elective upper limb surgeries were randomly allocated into two groups. Group A received 30 mL of 0.5% ropivacaine with 1 µg kg-1 dexmedetomidine, and group B received 30 mL of 0.5% ropivacaine with 1 µg kg-1 fentanyl for supraclavicular brachial block. The onset and duration of sensory and motor block and adverse events during the perioperative period were noted. Results: The onset of sensory and motor blockade was 13.47±1.73 min and 22.87±2.27 min respectively in the dexmedetomidine group and 14.80±2.20 min and 24.33±2.63 min respectively in the fentanyl group which was statistically significant (P<0.05). The duration of the sensory blockade was significantly higher in the dexmedetomidine group as compared with fentanyl (826±58.29 vs 592±51.62 minutes, p< 0.0001). Conclusions: Dexmedetomidine provides faster onset of sensory and motor block with longer duration of block as compared with fentanyl when used as an adjuvant with ropivacaine in supraclavicular brachial plexus block without any significant side effects.